2021
DOI: 10.1021/acs.jafc.1c03092
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Enzymatic Synthesis of Lipophilic Phenolic Glycoside Azelaic Acid Esters and Their Depigmenting Activity

Abstract: In this paper, an enzymatic route for synthesizing phenolic glycoside azelaic acid esters was successfully set up via lipase-catalyzed esterification and transesterification. Among the lipases tested, Candida antarctica lipase B (Novozyme 435) showed the highest activity in catalyzing esterification and Thermomyces lanuginosus (Lipozyme TLIM) gave the highest substrate conversion in catalyzing transesterification for the synthesis of ester. The addition of 4A molecular sieves into the reaction system is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…7 Fortunately, a diet of natural active compounds with α-glucosidase inhibitory activity, such as anthocyanins, 8 flavonoids 9 and fatty acids, 10 has been proven to be a safe and effective way to control hyperglycemia. 11 Phlorizin (C 21 H 24 O 10 , phloretin-2′-β-D-glucopyranoside) and polydatin (C 20 H 22 O 8 , 3,4″,5-trihydroxystilbene-3-β-D-glucopyranoside) are antioxidant phenolic glycosides and have a variety of beneficial in vivo biological activities, 12 such as anti-inflammation, anti-fatigue, hepatoprotection, etc. However, only a few studies reported the in vitro inhibition activity of phlorizin against α-glucosidase.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Fortunately, a diet of natural active compounds with α-glucosidase inhibitory activity, such as anthocyanins, 8 flavonoids 9 and fatty acids, 10 has been proven to be a safe and effective way to control hyperglycemia. 11 Phlorizin (C 21 H 24 O 10 , phloretin-2′-β-D-glucopyranoside) and polydatin (C 20 H 22 O 8 , 3,4″,5-trihydroxystilbene-3-β-D-glucopyranoside) are antioxidant phenolic glycosides and have a variety of beneficial in vivo biological activities, 12 such as anti-inflammation, anti-fatigue, hepatoprotection, etc. However, only a few studies reported the in vitro inhibition activity of phlorizin against α-glucosidase.…”
Section: Introductionmentioning
confidence: 99%
“…14 The α-glucosidase inhibition mechanism and hypoglycemic activity of phlorizin and polydatin in the intestine were indeed lacking. 15 In addition, we efficiently synthesized dodecyl-acylated derivatives of phlorizin and polydatin in a previous study, 12 and acylation was shown to enhance the tyrosinase inhibitory capacity of phlorizin and isoquercitrin. 16 Thus, the acylated derivatives of phlorizin and polydatin may exhibit stronger α-glucosidase inhibitory activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some avonoid glycoside esters have been approved as fat-soluble antioxidants for use in oils and other foods, such as propyl gallate and tea polyphenol palmitate [1]. Flavonoid glycoside esters exert excellent antioxidant effects, cellular absorption, and other biological activities than their parent compounds, such as lipid-lowering activity, antimicrobial activity, and antimelanogenic effect [2][3][4]. Therefore, avonoid glycoside esters could be used as potential functional active ingredients or additives in food, cosmetics, and nutraceuticals.…”
Section: Introductionmentioning
confidence: 99%